A Study on Retailer and Customer Attitude Towards P & G Detergent Powder in Coimbatore City - Thirumoorthi, P.; Karthikeyan, P. (Indian Journal of Marketing, 2006)
The study was undertaken to find out the Attitude towards P&G detergent Powders (Ariel and Tide) from Retailer and Customers. The study was carried out with 100 customers and 100 retailers were considered and their opinion about P&G detergent powder has been gathered. The primary data were collected through a structured questionnaire designed for retailers and customers. The data were consolidated and interpreted by using statistical tools like simple average, Ranking, Chi Square analysis and ANOVA. Tables and graphs are used for better representation. According to the result obtained from the opinion survey, it was found that P&G detergent powder is superior and market leader, in terms of quality and performance.